A Review of the Blended Teaching Reform in Nutritional Physiology Based on the “Project-Driven + Competition-Empowered” Model Under the OBE Concept - Li, Ning; Wang, Jiayi; Wang, Shiqiong; Gao, Xiaoping; Li, Tiange; Zhao, Peijun; Huang, Xianqing; Li, Qian (Journal of Educational Research and Policies, 2026)
Nutritional physiology, as a core course in the fields of food science and nutrition, serves as a crucial bridge connecting basic physiology with clinical nutrition practice. However, traditional teaching models have long faced practical challenges such as lagging content updates, monotonous teaching methods, disconnection between theory and practice, one-sided assessment and evaluation, and insufficient integration of ideological and political education. These issues make it difficult to meet the demands of the new era for cultivating interdisciplinary and innovative nutritional talents. To address these teaching dilemmas, this study, fundamentally guided by the Outcome-based Education (OBE) concept, systematically constructs a blended teaching model characterized by “Project-Driven + Competition-Empowered” learning. This model clarifies course competency objectives through backward design, uses progressive real-world projects as the driving mainline, leverages disciplinary competitions as the high-level outcome output, and relies on online-offline blended teaching environments to provide comprehensive support throughout the process. This article systematically reviews relevant literature on teaching reform, arguing for the scientific validity and feasibility of this model from three aspects: theoretical connotation, practical pathways, and implementation framework. Practice indicates that this model can effectively stimulate students’ intrinsic learning motivation, significantly enhance their comprehensive abilities such as knowledge integration, practical innovation, and teamwork, thereby providing a referable paradigm for applied course reform.